Stability improvement and characterization of bioprinted pectin-based scaffold. Issue 1 (February 2019) - Stealey, Samuel; Guo, Xiaoru; Ren, Lixia; Bryant, Elizabeth; Kaltchev, Matey; Chen, Junhong; Kumpaty, Subha; Hua, Xiaolin; Zhang, Wujie
Purpose: Bioprinting is an alternative method for constructing tissues/organs for transplantation. This study investigated the cross-linker influence and post-printing modification using oligochitosan and chitosan for stability improvement. Methods: Oligochitosan was tested as a novel cross-linker to replace Ca 2+ for pectin-based bio-ink. Oligochitosan (2 kD) and different molecular weight of chitosan were used to modify the bioprinted scaffold. Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM) were used to characterize the scaffolds. Results: Oligochitosan failed to serve as a viable cross-linker. Successful post-printing modification was confirmed by FTIR and SEM analyses. Conclusion: Regarding post-modification, chitosan-treated scaffolds showed enhanced stability compared to untreated scaffolds. In particular, scaffolds modified with 150 kD chitosan exhibited the highest stability.